Karakter Edible Film Ulva lactuca-kitosan sebagai Pengemas Bumbu Mi Instan - Sperisa Distantina; Nuril Nasdhofa Ayuni; Vivin Sulistyaningrum Yudha Sarjani (CHEMICA: Jurnal Teknik Kimia, 2018)
In this research, the edible films based on Ulva lactuca flour, chitosan, corn starch, and glycerol were prepared. The edible films was for wrapping of instant noodle seasoning. The aim of this research was to investigate the effect of weight ratio of Ulva lactuca flour-chitosan on the properties of the prepared edible flims. Innitialy, the mixture of Ulva lactuca flour, corn starch, and chitosan were stirred in acetic acid solution 1%. After the chitosan was dissolved, the glycerol was added. The mixture was heated at 80OC and stirred for 30 minutes. The obtained edible film solution was then poured into antisticky surface and dried at oven until a constant weight was attained. The dried films were characterized, including moisture content, E. coli resistivity, hydration index, thickness, and solubility in hot water. Based on experimental data, it was found that the best composition of edible film was 2 g Ulva lactuca flour, 2 g Chitosan, 2 g corn starch, 100 ml acetic acid 1%, and 1 mL glycerol.